2022
DOI: 10.3389/fneur.2022.663200
|View full text |Cite
|
Sign up to set email alerts
|

IE-Vnet: Deep Learning-Based Segmentation of the Inner Ear's Total Fluid Space

Abstract: BackgroundIn-vivo MR-based high-resolution volumetric quantification methods of the endolymphatic hydrops (ELH) are highly dependent on a reliable segmentation of the inner ear's total fluid space (TFS). This study aimed to develop a novel open-source inner ear TFS segmentation approach using a dedicated deep learning (DL) model.MethodsThe model was based on a V-Net architecture (IE-Vnet) and a multivariate (MR scans: T1, T2, FLAIR, SPACE) training dataset (D1, 179 consecutive patients with peripheral vestibul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 84 publications
0
5
0
1
Order By: Relevance
“…Although multi‐atlas segmentation could potentially contour the dural sac on CTM, the use of deformable image registration in this method could significantly impair segmentation performance in cases complicated by pathological lesions (e.g., severe LSS or scoliosis) 42 . Numerous studies have confirmed the advantages of DL algorithms over the atlas‐based segmentation methods especially when segmenting cases with pathological lesions 43–45 . Thus, we have implemented DL algorithms to develop an automatic contouring tool for the lumbar dura on CTM images.…”
Section: Discussionmentioning
confidence: 99%
“…Although multi‐atlas segmentation could potentially contour the dural sac on CTM, the use of deformable image registration in this method could significantly impair segmentation performance in cases complicated by pathological lesions (e.g., severe LSS or scoliosis) 42 . Numerous studies have confirmed the advantages of DL algorithms over the atlas‐based segmentation methods especially when segmenting cases with pathological lesions 43–45 . Thus, we have implemented DL algorithms to develop an automatic contouring tool for the lumbar dura on CTM images.…”
Section: Discussionmentioning
confidence: 99%
“…3D- or volumetric quantification of the ELS ( v ELS) was achieved in two steps: First, segmentation of the total fluid space (TFS) was based on IE-Vnet [ 33 ], a recently proposed and pre-trained volumetric deep learning algorithm with V-net architecture. IE-Vnet was deployed via the TOMAAT module [ 34 ] into the 3D–Slicer toolbox (version 4.11, [ 35 ]).…”
Section: Methodsmentioning
confidence: 99%
“…3D-quantification of the ELS consisted of three steps: first, segmentation of the total fluid space (TFS) was based on IE-Vnet [ 50 ], a recently proposed and pre-trained volumetric deep learning algorithm with V-net architecture that was deployed via the TOMAAT module [ 51 ] in a 3D–Slicer toolbox (version 4.11 [ 36 ]). Second, ELS and perilymphatic space (PS) were differentiated within the TFS using Vo lumetric L ocal T hresholding (VOLT; [ 52 ]) with ImageJ Fiji [ 53 ], the “Fuzzy and artificial neural networks image processing toolbox” [ 54 ], and the “MorphoLibJ Toolbox” [ 55 ].…”
Section: Methodsmentioning
confidence: 99%